Termites Grown on Seaweed Media as Dietary Source of Protein in the Diets of African Catfish (Clarias gariepinus) - Aniema P., Inyang-Etoh; U. , Eteng, Sunday; Philomena E., Asuquo; Caroline J., Odum (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A twelve-week feeding trial was conducted to examine the effect of termites (Macrotermes nigeriensis) grown on seaweed as a dietary protein source in the diets of African catfish (Clarias gariepinus). A total of 600 live African catfish specimens were used in the investigation, which were divided into four groups (ATD0, ATD1, ATD2, and ATD3) depending on their diets. The control diet (ATD0) comprised of commercial fishmeal (FM) and soybean meal (SBM) as protein sources in the ratio of 54FM:46SBM; For the three experimental diets (ATD1, ATD2, and ATD3), 60% of the crude protein was contributed by ATM either produced from termites raised on seaweed, elephant grass or both (50:50). Results show that daily weight gain was higher in fish fed termite meal (ATM) based diets, while feed conversion ratio and viscerosomatic index were higher in control group. Inclusion of ATM in diets of African catfish did not affect nutrient digestibility, enzyme activities, and total bile acid levels in the different portions of the digestive tract. Essential amino acids and mineral composition of whole fish also showed insignificant differences between experimental groups. However, fatty acid composition in whole fish fed diet without termite meal was significantly lower than those fed diets containing termites grown on seaweed. The study concludes that raising catfish on feed made from termites grown on seaweed can provide a good source of essential fatty acids with high bioavailability potential in African catfish.